Pengendalian Kualitas, Pendekatan Input-Proses-Output Produk Sayur Hidroponik Kangkung pada BSI Farm - Hawina Siti Alanasry; Lucky Safitri; Nur Azizah; Yolanika Cahyadi; Putri Imelda; Fany Apriliani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The main issue faced by BSI Farm is the suboptimal quality control at each stage of hydroponic kale production, resulting in inconsistent product quality. This study aims to analyze the quality of hydroponic kale products at BSI Farm using the input-process-output (IPO) approach. The analysis covers all stages of production, from the selection of superior seeds, nutrient and water management, cultivation using the NFT (Nutrient Film Technique) system, to harvesting and packaging. The results show that the implementation of strict quality control at each stage successfully produces fresh, clean, pesticide-free kale that meets modern market standards. Production waste is managed through a grading system and utilized as animal feed to minimize environmental impact. The main challenges include pest attacks, plant diseases, and inconsistent harvests due to a lack of standardized procedures. However, these can be addressed through regular monitoring, appropriate use of pesticides and fungicides, and consistent implementation of cultivation SOPs.